ANALYSING TEACHERS’ STRATEGIES FOR EFL CLASSES IN TEACHING LEARNING PROCESS IN THE MERDEKA CURRICULUM - KADEK ERNA YATININGSIH; LUH PUTU ARTINI; A.A GEDE YUDHA PARAMARTHA (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2024)
English as a foreign language should be taught in Indonesia, both formal and informal, as it is essential for competing in this globalisation era. The study proposed to (1) analyse the strategies applied by teachers in the Merdeka curriculum during the learning and teaching of EFL learners and (2) analyse students’ perception towards teachers’ strategies. It focused on analysing an English teacher and three students who role as the research subject. The study was specifically conducted at SMK Restumuning through a qualitative approach. The data were obtained qualitatively with a questionnaire, observation and documentation. The obtaining data were analysed and described qualitatively. The findings revealed that teachers applied two teaching strategies; autocratic teaching strategies and democratic teaching strategies. Students also perceive positively on teachers’ strategies during English learning in the Merdeka curriculum. Conclusively, autocratic and democratic strategies are appropriate for teaching English in vocational high schools.